Mentoring Teachers and Parents in Developing Literacy and Numeracy Educational Play Tools to Optimize Early Childhood Stimulation - Susanti, Siti Misra; Hartati, Hartati; Marwah, Marwah; Ariesta, Ariesta; Viola, Viola (TAAWUN, 2026)
The purpose of this activity is to improve the competence of teachers and parents in designing, making, and utilizing simple educational aids based on local materials and used goods. Through structured mentoring, participants are to be able to understand the concepts of literacy and numeracy early, and implement them through fun play activities at school and at home. The implementation method includes three stages, namely planning and preparation of mentoring materials, including surveying partner needs and preparing materials; the implementation of service and the practice of making educational teaching aids, with training, demonstration, and direct practice activities; as well as evaluation and follow-up assistance, through observation, questionnaires, and reflection on the results of activities. The partners of the activity are teachers and parents of early childhood in Baubau City. The results of the activity showed an increase in teachers’ and parents’ understanding of the concept of literacy and early numeracy, an increase in skills in making educational toys made from local and used goods, and a stronger collaboration between teachers and parents in stimulating children at school and at home. This activity produces various educational game products that are ready to be used in learning and support the development of early childhood literacy and numeracy in a sustainable manner. The contribution of this activity lies in strengthening the capacity of the early childhood education community through a collaborative teacher-parent mentoring model, providing examples of good practices in the use of local materials and used goods as learning media, and developing a sustainable approach in stimulating contextual and applicative early childhood literacy and numeracy.